PENERAPAN ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN HARGA POKOK TARIF PENYEWAAN JASA KENDARAAN PADA PT. SERASI AUTORAYA - Kindangen, Fricilia; Morasa, Jenny; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Activity Based Costing (ABC) is a simple calculation system to determine the cost of a product / service on the basis that it is the activity that causes the cost to arise, not from the product and the product that consumes the activity, the indirect costs can be determined through the activity it passes and the costs for each activity are then charged the product on the basis of consumption of each product in the activity. The purpose of this study was to determine the application of the cost of vehicle rental using Activity Based Costing method at PT Serasi Autoraya. This study uses descriptive analysis method, which is done by interviews and documentation. The results showed a comparison between the methods used by PT Serasi Autoraya and the application of Activity Based Costing System. For the calculation of the cost of the rental vehicle using Activity Based Costing System, namely for the type of Avanza car Rp. 3,710,271 and for Innova cars Rp. 6,567,413. There is a lower price difference between the calculation of PT Serasi Auotaraya and the results of calculations using Activity Based Costing System, namely for the Avanza Rp. 1,864,750 and for the Innova type there is a difference in the price of Rp. 1,313,728.Keywords: cost of rental service vehicle, Activity Based Costing System